Effect of HVTL Phase Transposition on Pipelines Induced Voltage - Kazeem Bolade Adedeji (IAES Indonesian Section, 2016)
In this work, a study of the effect of the phase conductor transposition for a multi-circuit high voltage power transmission lines on the induced voltage on a buried pipeline was conducted and considered through modelling. The modelling was done applying Carson’s concept of mutual impedances for a double circuit, three circuits and four circuit power transmission line on a buried pipeline. The simulated results obtained showed that the transmission line with un-transposed phase combination has the greater effect on the induced voltage while for the one or more of the other combinations, a cancellation or reduction can occur. This also is dependent on the tower geometry and the relative position of the pipeline and the transmission line. Also, the magnitude of the induced voltage increases with increasing number of circuits.